3D electron microscopy and volume-based bouton sorting reveal the selectivity of inputs onto geniculate relay cell and interneuron dendrite segments - Maher, Erin E.; Briegel, Alex C.; Imtiaz, Shahrozia; Fox, Michael A.; Golino, Hudson; Erisir, Alev (Frontiers in Neuroanatomy, 2023)
The visual signals evoked at the retinal ganglion cells are modified and modulated by various synaptic inputs that impinge on lateral geniculate nucleus cells before they are sent to the cortex. The selectivity of geniculate inputs for clustering or forming microcircuits on discrete dendritic segments of geniculate cell types may provide the structural basis for network properties of the geniculate circuitry and differential signal processing through the parallel pathways of vision. To reveal the patterns of input selectivity on morphologically discernable relay cell types and interneurons, we took advantage of Scanning Blockface Electron Microscopy (SBEM) technology and examined serial image stacks from the binocular core of the lateral geniculate nucleus. First, using unbiased data collection and statistical modeling approaches, we identified the criteria for volume-based sorting of geniculate boutons into their putative origins. Retinal terminals, initially identified by their unique mitochondrial morphology, displayed distinct subpopulations that can be further sorted by their volume distributions. Terminals deemed non-retinal based on the morphological criteria consisted of five distinct subpopulations, including small-sized putative corticothalamic and cholinergic boutons, two medium-sized, putative GABAergic inputs, and a large-sized bouton type that contains dark mitochondria. These criteria were then applied to a dataset of terminals that synapse on reconstructed segments of relay cells and a dataset of interneuron dendrites. Using a network analysis approach, we found an almost complete segregation of retinal and cortical terminals on putative X-type cell dendrite segments characterized by grape-like appendages and triads. On these cells, interneuron appendages intermingle with retinal and other medium size terminals to form triads within glomeruli. In contrast, a second, presumed Y-type cell displayed dendrodendritic puncta adherentia and received all terminal types without a selectivity for synapse location; these were not engaged in triads. The contribution of retinal and cortical synapses received by X-, Y- and interneuron dendrites differed such that over 60% of inputs to interneuron dendrites were from the retina, as opposed to 20% and 7% to X- and Y-type cells, respectively. The results underlie differences in network properties of synaptic inputs from distinct origins on geniculate cell types.